Pelatihan Digital Marketing Bagi Pelaku Usaha Mikro Kecil Menengah (UMKM) dengan Facebok Ads - Saehan, Andi; Nasution, Muhammad Bobbi Kurniawan; TriaNovie, Sri (Jurnal Pengabdian Masyarakat Gemilang (JPMG), 2024)
The use of Facebook Ads in digital marketing training for MSMEs has become an important approach in improving digital marketing capabilities. Several trainings have discussed digital marketing strategies, including the use of Facebook Ads, to support MSME products so they can compete more effectively. This training aims to help MSMEs understand digital marketing concepts, the use of social media, and content management, as well as to overcome price challenges and market competition. Thus, this training provides a strong foundation for MSMEs to utilize Facebook Ads and other digital marketing strategies in an effort to expand their brand's market reach.